Woody and Herbaceous Species Diversity Respond Differently to Environmental Variables in Semiarid Areas in Ghana - Reginald T. Guuroh; Bertrand F. Nero; Fousseni Folega; Kwame A. Oduro; Fred Kalanzi; Gloria K. Adeyiga; Adu‐Gyamfi Asamoah; Mark Appiah; Miracle Obeng; E. Amponsah (Ecology and Evolution)
ABSTRACT In the semiarid areas of Ghana, the interactive effects of various environmental drivers, their relative importance, and their direct and indirect effects on plant species composition and diversity are still poorly understood, hence affecting effective ecosystem management. Using a combined gradient approach, the study investigated the predictors of species diversity of both the woody and the herbaceous layers of a steep land‐use and climatic gradient from the forest‐savanna transition to the Sudan savanna of Ghana. Species richness and the Shannon–Weiner Index are the response variables. Two‐way ANOVA was performed to test the interaction effects of climate and land‐use on species diversity; linear mixed‐effect models were used to test the relationships between multiple environmental variables, and structural equation modelling was used to determine the direct and indirect effects of climate and land‐use on species diversity. We found significant effects of climate and land use, and their interactions on species diversity for both vegetation layers. We also found differential responses of the herbaceous and woody layers to environmental drivers. Land use (Grazing pressure) was the most important predictor of the woody layer while climatic aridity was the most important for the herbaceous layer. Climatic aridity and fire were only directly important for herbaceous vegetation but not the woody layer, although their indirect effects cannot be discounted. For soil properties, organic matter was important for both vegetation layers. Synthesis: The marked differences in species composition for various land uses along the climatic gradient imply that climate change will indeed affect vegetation. The observed importance of grazing for all response variables implies that land use could override climate effects and that appropriate land management strategies could mitigate potential negative effects of climate change.